1977
DOI: 10.1063/1.433901
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motions in compressed liquid heavy water at low temperatures

Abstract: The NMR deuteron spin–lattice relaxation times T1, self-diffusion coefficients D, and shear viscosities η have been measured as a function of pressure in the temperature interval −15 to 10°C. The low-pressure extreme of the measurements is Ice I, whereas Ice V represents the high-pressure boundary of the experiments. In analogy with anomalous motional behavior in compressed liquid water, the initial compression of liquid D2O in the temperature interval studied results in higher motional freedom of D2O molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…Several studies of dielectric (33,34) and NMR relaxation (35)(36)(37) in liquid H 2 0 and D 2 0 indicated that the Debye equation describes well the temperature dependence of the reorientation of water molecules at atmospheric pressure. However, the results of high-pressure studies (29,30,38) show convincingly that the Debye equation fails to account for the density effects on reorientation of water molecules. One has to conclude that the success of the Debye equation for reorientation of water at 1 bar is accidental.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies of dielectric (33,34) and NMR relaxation (35)(36)(37) in liquid H 2 0 and D 2 0 indicated that the Debye equation describes well the temperature dependence of the reorientation of water molecules at atmospheric pressure. However, the results of high-pressure studies (29,30,38) show convincingly that the Debye equation fails to account for the density effects on reorientation of water molecules. One has to conclude that the success of the Debye equation for reorientation of water at 1 bar is accidental.…”
Section: Resultsmentioning
confidence: 88%
“…In several studies (29,30) we took advantage of the phase diagram of water and heavy water and measured various transport properties of these liquids down to temperatures of -15°C. Nuclear magnetic resonance spin-lattice relaxation time Ti, self-diffusion coefficients, and shear viscosities were measured as a function of pressure in the temperature interval -15°C to 30°C.…”
Section: Resultsmentioning
confidence: 99%
“…ðTÞ is assumed to obey an Arrhenius behavior like liquid H 2 O and have a magnitude determined by the fitting of the experimental results [28][29][30]: …”
Section: Cross-section Modelmentioning
confidence: 99%
“…should lower to 204 kHz which is close to our value. Different authors have claimed the CDQc to be independent of temperature [9,18] and only slightly decreasing with increasing density [8,9,35,36]. We therefore assume a constant value of the CDQC over the range of temperatures and pressures measured.…”
Section: ) Estimate Of the Deuterium Quadrupole Coupling Constant ( mentioning
confidence: 99%